Análise de viabilidade para o investimento industrial em energia solar fotovoltaica em uma empresa de grande porte do setor metal mecânico - Botezeli, Luydi Kunzler (2023)
The studies related to alternative energy management with renewable sources of energy generation are increasingly becoming a necessary and urgent agenda to address the exponential increase in energy consumption worldwide, in accordance with environmental and sustainable requirements for the sector. With proper management of the integration of distributed energy resources in industrial consumers, several positive aspects emerge concerning quality and reliability, not only for the consumer but also for the distribution system and the environment. The study contributes to advancing knowledge in the use of photovoltaic solar energy alternatives in an industry, which encourages the reduction of non-renewable sources in the Brazilian energy matrix. In this context, this dissertation evaluates the current energy consumption situation and the implementation of a photovoltaic solar energy generation system in a large-scale industry with the aim of reducing expenses on electrical energy, seeking opportunities through energy management behind the meter, and addressing Environmental, Social, and Corporate Governance (ESG) considerations, which are particularly important in the current state of the planet. To do this, the current scenario of energy procurement environments in Brazil is presented, along with business models for energy self-production and energy storage, applied to the case study. Initially, local characteristics were collected to analyze the influence of meteorological variables such as radiation and temperature. Subsequently, different photovoltaic generation scenarios for the industry under study were analyzed, taking into account the minimum to maximum investment by the company. Finally, the financial data for each scenario were analyzed to assess the feasibility of investments within the scope of application in a company. This study received support from the Academic Master's and Doctorate Program for Innovation (MAI/DAI) from CNPq, the third-party company responsible for energy management in the analyzed company, and the internal financial sector of the industry in question.